First Report of Botryosphaeria dothidea Bark Split and Canker Disease in Eucalyptus Clone No. 413 from Haryana, India - Chandra, Suresh; Chander, Jagdish; Harsh, N. S. K. (Indian Forester, 2016)
Eucalyptus clone No. 413 which is being planted in a big way all over north India has been found attacked by a bark split and canker disease in farmers' fields. The disease has been studied in detail and is found to be caused by Botryosphaeria dothidea. The damage was assessed and suitable control measure was developed.